Early intervention and evaluation for adult‐onset psychosis: the JCEP study rationale and design. Issue 3 (28th February 2013) - Hui, Christy L.M.; Chang, Wing C.; Chan, Sherry K.W.; Lee, Edwin H.M.; Tam, Wendy W.Y.; Lai, Dik C.; Wong, Gloria H.Y.; Tang, Jennifer Y.M.; Li, Frendi W.S.; Leung, Kwok F.; McGhee, Sarah M.; Sham, Pak C.; et al.
Abstract Aim Psychotic disorders incur substantial long‐term burdens to patients and society. Early intervention (EI) during the initial years of psychotic disorders can improve long‐term outcome. In Hong Kong, a pilot EI programme (EASY, Early Assessment Service for Young people with psychosis) had been set up since 2001 to serve clients under 25 years of age. Although EASY has been effective in improving outcome, consolidation of early psychosis work requires further development. Methods The present paper describes a new EI development which targets adult patients with psychosis in Hong Kong. The Jockey Club Early Psychosis (JCEP) project was launched in 2009. Expanding the service to patients above 25 years old, JCEP aims to deliver a territory‐wide specialized EI service to adult‐onset psychosis patients, to promote public awareness on early psychosis, and to research on the optimal intervention model and duration for early psychosis in a 4‐year randomized controlled trial (RCT). Participants were randomly assigned to receive either 4 years of EI service, 2 years of EI service, or 4 years of standard care. Their symptoms, neurocognitive functions, psychosocial well‐being and health economics were regularly assessed. Results To date, 360 patients were recruited into the RCT, and 740 patients were recruited in a 2‐year naturalistic study. Prospective, longitudinal follow‐up assessments of these patients are still underway. Conclusions JCEP is the first EI project to provide adult early psychosis service in Chinese population. Future data would help to address the optimal duration of EI and its cost‐effectiveness. This would also assist regional and international mental health development.